The role of family history of depression and the menopausal transition in the development of major depression in midlife women: Study of women's health across the nation mental health study (SWAN MHS). Issue 9 (10th May 2017) - Colvin, Alicia; Richardson, Gale A.; Cyranowski, Jill M.; Youk, Ada; Bromberger, Joyce T.
Abstract : Background: This study evaluated whether family history of depression predicts major depression in midlife women above and beyond static risk factors (such as personal history of depression prior to midlife) and risks that may change dynamically across midlife (such as menopausal, psychosocial, and health profiles). Methods: Participants were 303 African American and Caucasian women (42–52 years at baseline) recruited into the Study of Women's Health across the Nation (SWAN) Mental Health Study (MHS) in Pittsburgh. Major depression was assessed annually with Structured Clinical Interviews for DSM‐IV . Family mental health history was collected at the ninth or tenth annual follow‐up. Random effects logistic regression was used to assess the relationship between family history of depression and midlife depression, controlling for baseline sociodemographic characteristics and time‐varying risk factors. Results: Family history of depression was associated with midlife depression after adjusting for participant's history of major depression prior to midlife, trait anxiety and baseline age, and time‐varying menopausal status, body mass index, very upsetting life events, and chronic difficulties (OR = 2.24, 95% CI = 1.17–4.29, P = .02). Higher odds of major depression were found when women were late perimenopausal or postmenopausal relative to when they were premenopausal or early perimenopausal (OR = 3.01, 95% CI = 1.76–5.15, P < .0001). However, menopausal status was only associated with major depression among women without a family history. Conclusions: Family history of depression predicts major depression in midlife women independent of the menopausal transition and other time‐varying covariates. Notably, the menopausal transition was associated with increased risk only among women without a family history of depression.